Incident Gout: Risk of Death and Cause-Specific Mortality in Western Sweden: A Prospective, Controlled Inception Cohort Study - Dehlin, Mats; Sandström, Tatiana Zverkova; Jacobsson, Lennart TH (Frontiers in Medicine, 2022)
Background Excess mortality in gout has been attributed to cardiovascular disease (CVD). In the light of decreased CVD-mortality in general we wanted to evaluate overall mortality in gout and cause-specific contributions to mortality beyond CVD and temporal trends. Methods All incident cases of gout between 2006-2015 in western Sweden and 5 population controls per case matched on age, sex and county were identified. Comorbidities were identified for 5 years preceding index date. Follow-up until death, migration or study end 31 of December 2017. Effect of gout on death risk was calculated using COX regression on whole population and stratified by sex, adjusted for demographics and comorbidities. Death incidence rate were compared between the two time periods, 2006-2010 and 2011-2015. Results We identified 22055 cases of incident gout and 98 946 controls, mean age (SD) 67.3-66.3 (15.3-15.4) years and 67.6-66.5% males. Except for dementia, all comorbidities were more common at baseline among gout cases. Overall risk for death in incident gout was increased with 3%; death by CVD, renal disease and digestive system was significantly increased while death by dementia and cancer was significantly decreased. There were no significant differences in incident death rate ratios between cases and controls in the two time periods examined. Conclusions A 3% increase in all-cause death in patients with gout highlights the importance of addressing not only CVD risk factors in gout management. Gout was associated with reduced mortality from dementia which may have implications on urate lowering therapy and possible effects on dementia risk.